1996
DOI: 10.1021/jp961285y
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopic Observation of Acrylic Acid Coadsorbed in Dissociated and Molecular Forms on Oxidized Aluminum

Abstract: Vibrational spectra from monolayer films of acrylic acid (CH 2 CHCOOH) on oxidized aluminum are obtained by inelastic electron tunneling spectroscopy and multiple reflection-absorption infrared spectroscopy. Analysis of these spectra shows that acrylic acid does not adsorb exclusively by a dissociative mechanism as do most carboxylic acids. Instead, at least two coadsorbed forms are observed: physisorbed molecular acid and chemisorbed acrylate ion. Rinsing the dosed surface with ethanol removes the physisorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The main peaks at 1067, 1263, 1373, 1448, 1519, and 1637 cm -1 are consistent to those of acrylate reported previously. 23,24 At 300 °C, these peaks are still present. As compared to the 300 °C spectra of Figures 1 and 2, which lack the characteristic acrylate bands at 1263 (υ(C-C)), 1373 (δ(C-H)), and 1637 (υ(CdC)) cm -1 , it is concluded that thermal decomposition of lactic acid on TiO 2 is unlikely to proceed via acrylic acid or acrylate by a dehydration process.…”
Section: Adsorption Of Pyruvic Acid and Acrylicmentioning
confidence: 94%
“…The main peaks at 1067, 1263, 1373, 1448, 1519, and 1637 cm -1 are consistent to those of acrylate reported previously. 23,24 At 300 °C, these peaks are still present. As compared to the 300 °C spectra of Figures 1 and 2, which lack the characteristic acrylate bands at 1263 (υ(C-C)), 1373 (δ(C-H)), and 1637 (υ(CdC)) cm -1 , it is concluded that thermal decomposition of lactic acid on TiO 2 is unlikely to proceed via acrylic acid or acrylate by a dehydration process.…”
Section: Adsorption Of Pyruvic Acid and Acrylicmentioning
confidence: 94%
“…29,30,62,102 Vibrational spectra were obtained using IETS and MRAIRS to study monolayers of pyruvic acid adsorbed on alumina incorporated in thin film Al/alumina/pyruvic acid/Pb samples. Spectra obtained using both techniques do not exhibit a carbonyl peak, however MRAIR spectra for similar samples without a Pb cover film do show the carbonyl stretch.…”
Section: Organic Compoundsmentioning
confidence: 99%
“…The mode of adsorption of carboxylic acids and their corresponding polymers onto mineral surfaces has been studied extensively using many spectroscopic techniques, including X-ray photoelectron, inelastic electron tunneling, and Mössbauer spectroscopies. Infrared spectroscopic techniques such as diffuse reflectance (DRIFT) and polarized grazing angle (PGA) have also been popular choices because the molecular vibrations associated with the carboxylate functionality offer considerable potential for identifying its binding mode.…”
Section: Introductionmentioning
confidence: 99%